Year in review 2022: Big changes proposed for field. Issue 1 (30th December 2022) - Knopf, Alison
Abstract : The end of 2022 saw a culmination of many reforms addiction treatment providers have long fought for, mainly, proposals by the Substance Abuse and Mental Health Services Administration (SAMHSA) to reform methadone treatment by keeping opioid treatment programs (OTPs) in control but making it easier for patients to get take‐homes; and a vast spending bill signed into law by President Biden at the very end of the year that allows buprenorphine to be prescribed without a waiver, and much more (see page 3).